The long‐term risk of upper‐extremity lymphedema is two‐fold higher in breast cancer patients than in melanoma patients. Issue 8 (18th October 2015) - Voss, Rachel K.; Cromwell, Kate D.; Chiang, Yi‐Ju; Armer, Jane M.; Ross, Merrick I.; Lee, Jeffrey E.; Gershenwald, Jeffrey E.; Stewart, Bob R.; Shaitelman, Simona F.; Cormier, Janice N.
Abstract : Background and Objectives: We assessed the cumulative incidence, symptoms, and risk factors for upper‐extremity lymphedema in breast cancer and melanoma patients undergoing sentinel lymph node biopsy or axillary lymph node dissection. Methods: Patients were recruited preoperatively (time 0) and assessed at 6, 12, and 18 months postoperatively. Limb volume change (LVC) was measured by perometry. Lymphedema was categorized as none, mild (LVC 5–9.9%), or moderate/severe (LVC≥10%). Symptoms were assessed with a validated lymphedema instrument. Longitudinal logistic regression analyses were conducted to identify risk factors associated with moderate/severe lymphedema. Results: Among 205 breast cancer and 144 melanoma patients, the cumulative incidence of moderate/severe lymphedema at 18 months was 36.5% and 35.0%, respectively. However, in adjusted analyses, factors associated with moderate/severe lymphedema were breast cancer (OR 2.0, P  = 0.03), body mass index ≥30 kg/m 2 (OR 1.6, P  = 0.04), greater number of lymph nodes removed (OR 1.05, P  < 0.01), and longer interval since surgery (OR 2.33 at 18 months, P  < 0.01). Conclusions: Lymphedema incidence increased over time in both cohorts. However, the adjusted risk of moderate/severe lymphedema was two‐fold higher in breast cancer patients. These results may be attributed to surgical treatment of the primary tumor in the breast and more frequent use of radiation. J. Surg. Oncol. 2015;112:834–840 . © 2015 Wiley Periodicals, Inc.